Return to work guidelines for the COVID-19 pandemic - Rueda-Garrido, Juan Carlos; Vicente-Herrero, Mª Teofila; Campo, Mª Teresa del; Reinoso-Barbero, Luis; Hoz, Rafael E de la; Delclos, George L; Kales, Stefanos N; Fernandez-Montero, Alejandro (Occupational medicine (Oxford, England), 2020)
The novel coronavirus 2019 or SARS-CoV-2 has spread worldwide since first being detected in China in December 2019. It has been declared a global health emergency by the World Health Organization [1], and public health measures have been applied, including social distancing, work restrictions and home-working promotion. As many countries have flattened the epidemic curve, they are now examining strategies to reopen their economies, requiring evidence-based strategies to return workers to their jobs in the safest way possible. Occupational physicians can play key roles in monitoring workers’ health and developing effective return to work guidelines. Along with clinical presentation, laboratory tests provide added value to confirm the diagnosis and the stage of COVID-19.
Keywords: pandemic; COVID-19; Scopus(2); JCR